Endoscopic evaluation of small bowel lesions in Hodgkin's lymphoma patients during chemoradiation therapy - D. A. Khomov; Yu. V. Sinev; V. VM. Sotnikov (Онкогематология)
Our article shows first experience of using capsule endoscopy for examination of small bowel’s lesions in case of radiation therapy and chemotherapy in patients with Hodgkin lymphoma. We try to compare these changes with modern theories of normal tissues response to radiation therapy and chemotherapy. The investigation revealed that more than a half of the patients (58%) had not any clinical symptoms of small bowel iatrogenic lesions, including potentially dangerous late strictures.